The role of foreign reserves in inflation dynamics - Kuncoro, Haryo (Universitas Islam Indonesia, 2024)
Purpose – Central banks’ foreign reserve stocks in emerging markets have increased substantially in recent decades. Foreign reserves accumulation has been widely believed as a shock absorber to prevent financial crises. Meanwhile, accelerating foreign reserves might be contradictory to the monetary policy objectives. This research aims to investigate the impact of foreign reserves on the inflation dynamics.Method – We apply the inflation-expectation augmented Phillips curve on the monthly data over the period of 2005(7) to 2020(12) in the case of Indonesia. Findings – We show that stockpiling foreign exchange reserves indeed has an inflationary pressure impact. The central bank's intervention in the foreign exchange market is more significant in selling rather than purchasing foreign exchange. However, the non-monetary factors also play an important role in determining inflation. Implications – Considering channels through which foreign reserves might affect inflation, our findings suggest the monetary authority should be concerned with inflationary expectations in the short term as one of the major policy-driven goals to maintain price stability in the long run.Originality – This paper contributes to the literature on monetary policy in developing countries. Unlike other empirical studies, this research employs the inflation-expectation augmented Phillips curve and accommodates the issue of asymmetric effects of the change in foreign reserves.